3x-1+5.3x-1=162
=>3x-1.(1+5)=162
=>3x-1.6=162=>3x-1=162:6=27=33
=>x-1=3=>x=4
5x+5x+2=650
=>5x+5x.52=650
=>5x.(1+25)=650
=>5x.26=650=>5x=650:26=25=52
=>x=2
3x-1+5.3x-1=162
=>3x-1.(1+5)=162
=>3x-1.6=162=>3x-1=162:6=27=33
=>x-1=3=>x=4
5x+5x+2=650
=>5x+5x.52=650
=>5x.(1+25)=650
=>5x.26=650=>5x=650:26=25=52
=>x=2
Tìm số tự nhiên x biết rằng
a) \(5^x+5^{x+2}=650\)
b) \(3^{x-1}+5.3^{x-1}=16\)
tìm số tự nhiên x biết rằng
a. 5x + 5x+2 = 650
b. 3x-1 + 5.3x-1 =162
a) 5x + 5x+2 = 650
b) 3x-1 + 5.3x-1 = 162
a)\(5^x+5^{x+2}=650\)
b)\(3^{x-1}+5.3^{x-1}=162\)
5x+5x+2=650
b)3x-1+5.3x-1=162
(giup voi hic hic :'( )
Tìm số hữu tỉ x biết
(2x-1)6=(2x-1)8
Tìm số tự nhiên x
5x+5x+2=650 3x-1+5.3x-1=162
a) (2x-1)^3=27
b) (2x-1)^4=81
c) (x-2)^5=-32
d) (3x-1)^4=(3x-1)^6
đ) 5^x +5^x+2=650
g) 3^x-1 +5.3^x-1=162
a, \(5^x+5^{x+2}=650\)
b, \(3^{x-1}+5.3^{x-1}=162\)
TÌM X BIẾT
a, \(\frac{\left(37\frac{3}{7}-35\frac{2}{5}\right).9^9+36.27^5}{71.3^{17}.\left(x-0.25\right)}=\frac{1}{21}+\frac{1}{27}+\frac{1}{165}\)
b, \(\left(\frac{3}{4}\right)^x=\frac{2^8}{3^4}\)
c, \(5^x+5^{x+2}=650\)
d,\(3^x.3^{-1}+5.3^{x-1}=162\)